Eklesiologi Martin Luther sebagai Dasar Teologi Tata Gereja di GKPI - Ronald Patiar Hutabarat; Rencan C. Marbun (Sepakat : Jurnal Pastoral Kateketik, 2025)
Understanding ecclesiology plays a crucial role in the structure and life of the church, because through ecclesiology, the church can recognize its identity and understand its purpose and calling in the world. Proper ecclesiology is the basis for the formation of church organizations and the implementation of religious practices. With this understanding, the church can carry out its function as a community of faith that reflects the love and truth of Christ in life together. GKPI is one of the churches that adheres to Luther's ecclesiology. This study aims to see how the ecclesiology understood by Martin Luther is used as the basis for the theology of church order in GKPI.